2021
DOI: 10.1096/fj.202001063r
|View full text |Cite
|
Sign up to set email alerts
|

Haploinsufficient tumor suppressor PRP4K is negatively regulated during epithelial‐to‐mesenchymal transition

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri butio n-NonCo mmerc ial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 51 publications
(143 reference statements)
0
6
0
Order By: Relevance
“…CTGF, CRY61, ANKRD1 and AJUBA) ( Figure 4 ). Similarly, Clarke et al (2021) found that PRP4K knockdown promotes transformed breast cancer cell migration and invasion, yet appeared to inhibit 2D cell migration in non-transformed MCF10A cells. Thus, transformation state of the cell may play an important role in physiological outcome of PRP4K depletion in regard to enhanced cell migration and invasion.…”
Section: Prp4k As a Cancer Biomarker And Haploinsufficient Tumour Sup...mentioning
confidence: 85%
See 3 more Smart Citations
“…CTGF, CRY61, ANKRD1 and AJUBA) ( Figure 4 ). Similarly, Clarke et al (2021) found that PRP4K knockdown promotes transformed breast cancer cell migration and invasion, yet appeared to inhibit 2D cell migration in non-transformed MCF10A cells. Thus, transformation state of the cell may play an important role in physiological outcome of PRP4K depletion in regard to enhanced cell migration and invasion.…”
Section: Prp4k As a Cancer Biomarker And Haploinsufficient Tumour Sup...mentioning
confidence: 85%
“…Several studies have now demonstrated that PRP4K regulation of YAP is a conserved process between flies and mammals ( Cho et al, 2018 ; Clarke et al, 2021 ; Zhou et al, 2021 ). For example, Clarke et al (2021) showed that when EMT was induced by media containing transforming growth factor beta (TGFβ) or as a result of EIF3E loss in the non-transformed mammary cell line MCF10A, PRP4K expression was reduced ( Figure 4 ), and this correlated with increased YAP nuclear translocation and target gene expression in EIF3E-depleted MCF10A cells.…”
Section: Prp4k As a Cancer Biomarker And Haploinsufficient Tumour Sup...mentioning
confidence: 99%
See 2 more Smart Citations
“…AKR1B10 downregulated CDH1 expression via the PI3K/AKT/NF-κB p65 signaling pathway in MCF-7 cells ( 113 ). Moreover, taxane therapy resistance was related to reduced PRP4K expression, depletion of PRP4K in TNBC cells (MDA-MB-231), and enhanced 2D migration, and 3D invasion correlated with higher fibronectin levels rather than changes in CDH1 ( 114 ). Connexins linked to N-cadherin, vimentin, Snail, and Zeb1 modulate CSC and EMT properties in breast cancer cells ( 90 ).…”
Section: Cadherins and Endocrine-related Cancersmentioning
confidence: 99%